Daunorubicin associated to lipid core nanoparticles reduces atherosclerotic lesions, inflammation and cardiotoxicity in atherosclerosis rabbit model. (25th November 2020) - Albuquerque, C.I; Tavares, E.R; Guido, M.C; Lopes, N.M; Baroni, R.V; Jensen, L; Silva, B.M.O; Kalil-Filho, R; Tavoni, T.M; Maranhao, R.C
Abstract: Introduction: Antiproliferative agents used in cancer chemotherapy have low toxicity and increased pharmacological action when carried into lipid core nanoparticles (LDE). LDE has similar structure to LDL and binds to LDL receptors through apo E it acquires in contact with plasma. Previously, we showed that treatment of rabbits with atherosclerosis with drugs such as taxanes and etoposide associate to LDE had pronounced reduction of the atherosclerotic lesions. In this study, we hypothesized whether daunorubicin (DNR) that belongs to another class of anti-cancer drugs, with a distinct mechanism of action and that has strong cardiotoxicity could also have effects against atherosclerosis. Methods: Sixteen New Zealand male rabbits were fed with a 1% cholesterol diet for 8 weeks to induce atherosclerosis. After 4 weeks, the animals were treated weekly with LDE-DNR (6mg/kg, iv, n=9) or with LDE only (n=7). In addition, 3 animals without any intervention were used as a control group. Chow consumption, lipid and hematological profiles, body weight, and echocardiography were evaluated at baseline, pre-treatment and post-treatment. Morphometry and protein expression were performed to analyze the aortas. Results: There was no difference in food intake and body weight for control, LDE and LDE-DNR groups. Total cholesterol, HDL-C, non-HDL-C and triglycerides increased in LDE and LDE-DNR groups when comparing baseline and post-treatment. Red blood cells decreased in LDE group at post-treatment in comparison to baseline, while LDE-DNR presented no such difference. Regarding aortic lesions of LDE-DNR group was 50% lower than LDE group. The protein expression of the inflammatory markers CD68, TNF-α and IL-6 in LDE-DNR was lower than LDE. Pro-apoptotic factors caspase 3, caspase 9 and BAX were also lower in LDE-DNR compared to LDE. Protein expression of vascular endothelial growth factor (VEGF) and vascular cell adhesion molecule (VCAM) was lower in the LDE-DNR group when compared to the LDE group. To test the cardiotoxicity of LDE-DNR, echocardiography was performed and observed that under LDE-DNR both systolic and diastolic function were preserved with no difference in cardiac mass in LDE-DNR when compared to control and LDE groups. However, LDE showed a significant increase in relative heart weight compared to control while LDE-DNR had no such difference. Treatment with LDE-DNR did not induce observable hematological toxicity. Conclusion: The treatment with LDE-DNR reduced aortic lesions, diminished inflammatory and pro-apoptotic factors, diminished VCAM expression in the aorta and promoted cardiac preservation in a rabbit atherosclerosis model. In conclusion, LDE-DNR can be eligible for future developments in the quest for novel effective and safe treatments for atherosclerosis. Funding Acknowledgement: Type of funding source: Public grant(s) – National budget only. Main funding source(s): FAPESP (Fundaçao de Amparo a Pesquisa do Estado de Sao Paulo)